644 Improving VTE Prophylaxis in Spinal Patients – a Closed Loop Audit. (19th August 2022) - Ziolkowska, K; Ismail, N
Abstract: Aim: Venous thromboembolism (VTE) prophylaxis is one of the key components of safe patient care and can be particularly challenging when it concerns spinal admissions to the orthopaedic trauma ward. The first cycle of our closed loop audit aimed to assess the safety of VTE prescribing in spinal admissions at a district general hospital. The current cycle aims to evaluate guideline compliance following our interventions. Method: Quality of VTE prophylaxis prescribing was measured against NICE (NG89) recommendations as well as local guidelines. Patients were identified based on prospectively maintained admission lists. The initial audit cycle was presented locally, and the following measures were introduced in order to improve prescribing: staff teaching sessions, nomination of a VTE guardian, inclusion of VTE plans in op-notes, publication of a dedicated spinal guideline and addition of a spinal section into the trust principal VTE guideline. The current audit cycle identified 22 spinal admissions. Results: Out of the 22 patients, only one (4%) received inadequate VTE prophylaxis which is a significant improvement compared to the initial data (8 cases - 18%). Minor prescribing concerns were noted in three cases (14%) versus 15 cases (34%) in the first cycle. Overall, the re-audit proved that following departmental interventions the majority of patients received appropriate VTE prophylaxis with no prescribing or documentation errors (82% in the current cycle vs 48% initially). Conclusions: We have demonstrated that significant improvement in VTE prophylaxis prescribing can be achieved by the means of educating staff and introducing simple and cost-effective measures.